Benefits and Harm of Treatment with P2Y12 Inhibitors beyond 12 Months in Patients with Coronary Artery Disease - Larsen, Mads Lamm; Grove, Erik Lerkevang; Kristensen, Steen Dalby; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2020)
The trade-off between the benefits and harm of long-term (> 12 months) treatment with P2Y12 inhibitors in patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI) remains controversial. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. PubMed and Embase were searched without time restrictions to identify randomized controlled trials comparing > 12-month P2Y12 inhibition versus ≤ 12-month treatment in patients with acute coronary syndrome (ACS) or stable CAD undergoing PCI. A qualitative assessment was performed using the assessment tool from the National Heart, Lung, and Blood Institute of the National Institutes of Health. We performed a meta-analysis of the following endpoints: primary outcome (primarily major cardiovascular events), all-cause death, and major bleeding. Eight trials, comprising 40,218 patients, were included. Five studies were rated “good,” two studies “fair,” and one study “poor.” The meta-analysis showed that > 12-month P2Y12 inhibition significantly reduced the primary outcomes compared with ≤ 12-month treatment (hazard ratio [HR]: 0.85; 95% confidence interval (CI): 0.75–0.97; p = 0.01). No significant difference was demonstrated between groups in all-cause death (HR: 1.02; 95% CI: 0.76–1.36; p = 0.91) or major bleedings (HR: 1.26; 95% CI: 0.93–1.70; p = 0.14). I2 test showed low to moderate heterogeneity among the included studies (21.6–62.3%). This systematic review and meta-analysis therefore demonstrates a reduction in major cardiovascular events during extended P2Y12-inhibitor treatment beyond 12 months compared with ≤ 12 months in patients with ACS or stable CAD undergoing PCI. There was no significant difference in all-cause death or major bleedings.
Keywords: aspirin; coronary artery disease; dual antiplatelet therapy; Purinergic P2Y Receptor Antagonists